Two new species of Buenoa Kirkaldy, 1904 (Hemiptera: Heteroptera: Notonectidae) from the States of Amazonas and Roraima, Brazil - Barbosa, Julianna Freires; Nessimian, Jorge Luiz; Ferreira-Keppler, Ruth Leila (Zootaxa, 2010)
The genus Buenoa has 63 described species, and there are 13 species in the Northern region of Brazil. In this study we describe two new species: B. dilaticrus sp. nov. (Alto Alegre – State of Roraima and Barcelos – State of Amazonas), similar to B. tibialis Truxal, 1957, but distinguished mainly by the lateral expansion near the base of the lateral margin of the mid-tibia; and B. exilidens sp. nov. (Barcelos AM), similar to B. platycnemis (Fieber, 1851), B. mutabilis Truxal, 1953, and B. tumaquensis Padilla-Gil, 2010, distinguished by the rostral prong, chaetotaxy, and stridulatory area of fore femur and the number of stridulatory teeth on the fore tibia.